An Effective Method for Reducing Belly-Bursting in Frozen Oil Sardines - PERIGREEN, P. A.; GOVINDAN, T. K.; PILLAl, V. K. (Fishery Technology, 2025)
A dip treatment in 15% sodium chloride solution for 30 minutes prior to freezing was found to be effective in reducing belly bursting occurring during freezing and thawing of oil sardines. The effect of size and fat content of sardines on belly-bursting phenome non and storage characteristics of brine treated sardines have been studied.